Pengaruh Komunikasi Interpersonal Terhadap Kinerja Pegawai pada Kejaksaan Agung Bidang Pengawasan - Ajeng Ayu Saputri; Susi Dhewi (Comit: Communication, Information and Technology Journal, 2024)
Effective interpersonal communication is important to be implemented in all companies, especially government agencies, so that effective communication will result in optimal and efficient performance. This study aims to determine how much influence interpersonal communication has on employee performance at the Attorney General's Office of Supervision. The sample used was 70 respondents. The approach used was quantitative and data collection used non-probability by distributing questionnaires to employees of the Attorney General's Office for Supervision. The sampling technique uses a type of convenience sampling. Data collection by means of Google Form with a measurement scale of 5 points. The analysis technique used is a simple linear assisted by IBM SPSS V.26 software to test the validity and reliability, F test, individual significant test (t test) and the coefficient of determination. The results of this study prove that interpersonal communication has a positive and significant effect on employee performance at the Attorney General's Office in the area of ​​vigilance by 62.6%. However, it should be noted that these results can be considered from other factors that affect employee performance. This research can contribute to knowing the need for interpersonal communication in improving employee performance in agencies and organizations. So that it is expected to be used in improving interpersonal communication and achieving agency goals effectively.